Mode of delivery and offspring body mass index, overweight and obesity in adult life: a systematic review and meta-analysis. - Karthik Darmasseelane; Matthew J Hyde; Shalini Santhakumaran; Chris Gale; Neena Modi (PLoS ONE)
Background It has been suggested that mode of delivery, a potentially powerful influence upon long-term health, may affect later life body mass index (BMI). We conducted a systematic review and meta-analysis of the effect of Caesarean section (CS) and vaginal delivery (VD) on offspring BMI, overweight (BMI>25) and obesity (BMI>30) in adulthood. Secondary outcomes were subgroup analyses by gender and type of CS (in-labour/emergency, pre-labour/elective). Methods Using a predefined search strategy, Pubmed, Google Scholar and Web of Science were searched for any article published before 31(st) March 2012, along with references of any studies deemed relevant. Studies were selected if they reported birth characteristics and long-term offspring follow-up into adulthood. Aggregate data from relevant studies were extracted onto a pre-piloted data table. A random-effects meta-analysis was carried out in RevMan5. Results are illustrated using forest plots and funnel plots, and presented as mean differences or odds ratios (OR) and 95% confidence intervals. Results Thirty-five studies were identified through the search, and 15 studies with a combined population of 163,796 [corrected] were suitable for inclusion in the meta-analysis. Comparing all CS to VD in pooled-gender unadjusted analyses, mean BMI difference was 0·44 kg·m(-2) (0·17, 0·72; p = 0·002), OR for incidence of overweight was 1·26 (1·16, 1·38; p<0·00001) and OR for incidence of obesity was 1·22 (1·05, 1·42; p = 0·01). Heterogeneity was low in all primary analyses. Similar results were found in gender-specific subgroup analyses. Subgroup analyses comparing type of CS to VD showed no significant impact on any outcome. Conclusions There is a strong association between CS and increased offspring BMI, overweight and obesity in adulthood. Given the rising CS rate worldwide there is a need to determine whether this is causal, or reflective of confounding influences. Systematic review registration An a priori protocol was registered on PROSPERO (registration number: CRD42011001851).